Legal Protection of Consumers from Negligence of Medical Personnel (Case Study of Swapped Baby at Sentosa Hospital Bogor) - Dewi Aulia Salsabilla; Hanifah Febriani (Proceeding International Conference Restructuring and Transforming Law, 2024)
Errors or negligence of medical personnel in the case of switched babies at Sentosa Bogor Hospital in carrying out their profession are fatal, because these errors or negligence have a detrimental impact on patients, even though patients also have rights protected by consumer protection laws in Law Number 8 of 1999. This research will analyse the legal mechanism for the settlement of switched babies according to Law Number 8 of 1999, and also analyse the responsibilities of hospitals and medical personnel in the case of switched babies at Sentosa Bogor Hospital. This research uses a normative juridical approach method by researching using library materials or secondary data by conducting a search for legislation and literature related to the problem under study. The results of the study found that consumer protection in Article 4 of Law Number 8 Year 1999 concerning consumer rights as patients regulates the right to comfort, safety, and security of patients and the right to obtain protection, advocacy, and settlement efforts. Referring to this article of the Law can be used as a settlement of the case of a swapped baby in Bogor at Sentosa Hospital. As the responsibility of the hospital for the swapped baby, the law can be charged from the article, namely, business actors do not carry out Standard Operational Procedures (SOP), and contrary to article 8 juncto article 62 which is mentioned can be charged with a fine of 2 billion or imprisonment. The settlement of this case can be resolved by mediation with the police and Sentosa Hospital sanctioned 15 nurses with temporary dismissal.